Revascularization in ischemic heart failure with reduced left ventricular ejection fraction. The impact of complete revascularization - Pyka, Łukasz; Hawranek, Michał; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Heart failure is a growing problem worldwide, with coronary artery disease being the underlying cause of over two-thirds of cases. Revascularization in this group of patients may potentially inhibit the progressive damage to the myocardium and lead to improved outcomes, but data in this area are scarce. This article emphasizes the role of qualification for revascularization and selection of method (percutaneous coronary intervention vs. coronary artery bypass grafting) and subsequently focuses on the issue of completeness of revascularization in this group of patients.